Perancangan Interior Pusat Perbelanjaan Khusus Wanita di Surabaya dengan Konsep Elegant Beauty - Poppy F Nilasari, Metta Dewi Martino Dwi Nugroho (Intra, 2014)
This work design is motivated by womens need for shopping specially for a big city like Surabaya. This need would need to be facilitated. A Shopping center which have few retails and a place to relax is demand by women. Therefore, designing shopping center interior for women in Surabaya was made. The design theme is